A Study of Myanmar Students’ Motivation for Learning English at Mahachulalongkornrajavidyalaya University - Ven. Pannasara; Kanokkamalade , Veerakarrn; Klinchan, Nilratana (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The purpose of this study was to investigate the patterns of Myanmar students’ motivation for learning process in English language at Mahachulalongkorn rajavidyalaya University. The research examined the patterns of students’ motivation in terms of two motivational constructions which were instrumental motivation and integrative motivation. This research method in the study was both quantitative and qualitative methods. The numbers of 139 samples were selected out of 218 only Myanmar students. The participants in this study were randomly selected: 139 participants including 70 first-year Myanmar students who were Bachelor of Arts, and Master of Arts in academic year 2019-2020, and 69 second-year Myanmar students who were Bachelor of Arts, and Master of Arts, the faculty of Buddhism, Humanities, and IBSC in academic year 2019-2020 at Mahachulalongkornrajavidyalaya University. The data were analyzed by using Statistical Package for the Humanities for Windows, and presented in descriptive statistics for percentage, mean score and standard deviation and content analysis method. The results revealed that Myanmar students had higher level instrumental motivation than integrative motivation in learning process in English language at Mahachulalongkornrajavidyalaya University. Moreover, there were many reasons why Myanmar students study many subjects, such as the English language at Mahachulalongkornrajavidyalaya University. Many respondents had problems for learning process in English language at Buddhist Universities in Myanmar, such as the educational policies, traditional teaching methods. Especially, educational policies were not connected and collaborated each other Buddhist Universities in Myanmar. The results of interviews revealed from the situations of Myanmar students’ motivation in learning process in English language. Interestingly, the majority of Myanmar students showed their preference to study many subjects, such as the English language at Mahachulalongkornrajavidyalaya University than at Buddhist Universities in Myanmar. Finally, the research findings could contribute to develop learning process in English language and to be international standard of university at Buddhist Universities in Myanmar.